ADVERSE EFFECTS OF GLUCOCORTICOID THERAPY IN RHEUMATOID ARTHRITIS (Лучшие интеллектуальные исследования, 2025)
Abstract: Glucocorticoids are widely used in the management of rheumatoid arthritis (RA) due to their potent anti-inflammatory and immunosuppressive properties. While these agents offer significant symptomatic relief and are often used as bridging therapy alongside disease-modifying antirheumatic drugs (DMARDs), their long-term use is associated with a broad spectrum of adverse effects. This article reviews the most common complications linked to glucocorticoid therapy in RA patients, including osteoporosis, adrenal suppression, metabolic disturbances, cardiovascular risks, ocular disorders, gastrointestinal effects, neuropsychiatric symptoms, and increased susceptibility to infections. Recognizing and managing these complications is essential to optimize patient outcomes and minimize treatment-related risks. The article emphasizes the importance of individualized therapy, dose minimization strategies, and preventive measures to reduce the burden of glucocorticoid-induced side effects.